Spatial and temporal expression patterns of Osbpl2a and Osbpl2b during zebrafish embryonic development. (May 2016) - Liu, Chunyu; Yao, Jun; Wei, Qinjun; Xing, Guangqian; Cao, Xin
Abstract: Objective: The mutated OSBPL2 (OMIM:606731 ), encoding oxysterol binding protein-like protein 2, was recently identified as a novel causative gene for autosomal dominant nonsyndromic hearing loss (ADNSHL). We reported the expression patterns of Osbpl2 in zebrafish, in order to further understand the role of OSBPL2 in hearing formation and development. Methods: Zebrafish was used as an animal model, and the expression of Osbpl2 was investigated by whole mount in situ hybridization. Results: Bioinformatics analysis indicates that zebrafish has two homologues of Osbpl2 gene ( Osbpl2a and Osbpl2b ) and Osbpl2b is the orthologous gene of human OSBPL2 . No expression of Osbpl2a and Osbpl2b mRNA is detected at 75% epiboly. The zygotical expression of the two genes has not been started at 11-somite stage. At 24 h post-fertilization (hpf), both Osbpl2a and Osbpl2b are found at ventricle zone of brain, however, the expression level of Osbpl2a is higher than that of Osbpl2b . When embryos are 48 hpf, the expression level of Osbpl2a and Osbpl2b becomes higher at the ventricle zone. At 72 hpf, Osbpl2b is only found at liver primordium, while Osbpl2a is not detected anywhere obviously. At 96 hpf, Osbpl2b is found at pharyngeal arches, liver, digestive tract and otic vesicle, while Osbpl2a remains undetected. Conclusion: Osbpl2b was demonstrated to be the orthologous gene of human OSBPL2, which has strong maternal expression, while Osbpl2a was detected without obvious maternal expression. This work would contribute to the further study of the molecular mechanism and function of OSBPL2 implicated with ADNSHL.